Iron Oxide Nanoparticles as a Potential Iron Fertilizer for Peanut (Arachis hypogaea) - Rui, Mengmeng; Ma, Chuanxin; Hao, Yi; Guo, Jing; Rui, Yukui; Tang, Xinlian; Zhao, Qi; Fan, Xing; Zhang, Zetian; Hou, Tianqi; Zhu, Siyuan (Frontiers in Plant Science, 2016)
Nanomaterials are used in practically every aspect of modern life, including agriculture. The aim of this study was to evaluate the effectiveness of iron oxide nanoparticles (Fe2O3 NPs) as a fertilizer to replace traditional Fe fertilizers, which have various shortcomings. The effects of the Fe2O3 NPs and a chelated-Fe fertilizer (ethylenediaminetetraacetic acid-Fe; EDTA-Fe) fertilizer on the growth and development of peanut (Arachis hypogaea), a crop that is very sensitive to Fe deficiency, were studied in a pot experiment. The results showed that Fe2O3 NPs increased the root length, plant height, biomass, and SPAD values of peanut plants. The Fe2O3 NPs promoted the growth of peanut by regulating phytohormone contents and antioxidant enzyme activity. The Fe contents in peanut plants with Fe2O3 NPs and EDTA-Fe treatments were higher than the control group. We used energy dispersive X-ray spectroscopy (EDS) to quantitatively analyze Fe in the soil. Peanut is usually cultivated in sandy soil, which is readily leached of fertilizers. However, the Fe2O3 NPs adsorbed onto sandy soil and improved the availability of Fe to the plants. Together, these results show that Fe2O3 NPs can replace traditional Fe fertilizers in the cultivation of peanut plants. To the best of our knowledge, this is the first research on the iron oxide nanoparticles as the iron fertilizer.